Performance analysis of diverse environment based on RSSI localization algorithms in wsns - Livinsa, Z. Mary; Jayashri, S. (2013 IEEE Conference on Information and Communication Technologies, 2013)
Wireless sensor networks (WSNs) are widely used in many environments and adverse terrains. Location estimation of sensor nodes is still a crucial area of research because of new localization requirements. One of the main hurdles facing sensor localization in WSNs is accuracy. Many localization algorithms and techniques have been proposed to estimate the position of nodes. In this paper, we consider an RSSI (received signal strength indicator) range based localization algorithm that relies on measuring the received signal strength indicator for distance estimation. In this work, we conducted the experiments in outdoor and indoor environments to derive the path loss model. The result shows that the outdoor environment has the better distance estimation than an indoor environment. Hence we investigate the effect of varying the anchor node density on localization error with minimum number of anchor nodes thereby enhancing an accuracy of the network.